“Dinámica de los eventos climáticos extremos en la cuenca alta del río Pastaza - Merino Silva, Daniela Alejandra (2020)
Climate change is one of the most discussed topics today because the effects of these changes influence both social and environmental systems. This work was based on the evaluation of the dynamics of extreme climate events in the upper Pastaza River basin. For the fulfillment of the proposed objectives, it was necessary to collect information from time series of meteorological data (temperature, precipitation) obtained from INAMHI of 11 stations located within the study area between 1965 and 2014, in which statistical analyses were applied to determine the variability of rainfall and temperature; and the analysis of standardized index of droughts (SPI) for the determination of intensity, duration and frequency of droughts. As a result, it was obtained that the high basin of Pastaza river has an annual average of precipitation of 780 mm and a non-periodic behavior of rains, governed by a bimodal regime and annual average temperature of basin of 15.3°C. The identified negative anomalies are frequently presented throughout the study period and coincide with ENSO events of NIÑO influence. The application of the SPI index indicated that the drought phenomena occur with a wide range of variability from light to extreme droughts being the provinces of Cotopaxi (Pastocalle), Chimborazo (Alao), and Tungurahua (Pillaro) the ones of greater magnitude (extreme).